Analysis of Radicalism Critical Discourse in Facebook Social Media - Apriya Maharani Rustandi; Karim Suryadi; Leni Anggraeni (Jurnal Civicus, 2021)
Social Media as a new forum for users to exchange information. Social media provides facilities that are easy and fast for its users. This has become an opportunity for radical groups to instill radicalism with free discourse patterns, but it has moved towards religious and political dynamics today. Uncontrolled social media in sharing information that is not necessarily valid in its distribution will increasingly have an impact on the spread of radicalism discourse texts. This research is proposed to see the series of words and sentences used in the radicalism discourse text. This research can be useful for the government to regulate social media in terms of policy regulation. The text of radicalism discourse that exists in social media can be dissected using Teun A Van Djik's analysis model which divides it into three structures, first the macro structure, the superstructure and the micro structure. This analysis model will also reveal the ideology that underlies a text. The purpose of this study is to determine the macro structure, superstructure and micro structure in the text of radicalism discourse. The benefits gained are being able to provide knowledge about radicalism on Facebook social media, providing encouragement to prevent radicalism efforts and images to the government in formulating policies to use social media as a preventive measure and re-establishing de-radicalization activities.